Effect of BaAl2O4 addition on power consumption and oxygen sensing response of Er123 ceramic rods utilizing hot-spot phenomenon - Hassan .M,; Yahya .A.K,; Okamoto .T, (Universiti Kebangsaan Malaysia, 2011)
In this paper, we report the effect of BaAl2O4 addition (0-30 wt. %) on power consumption and oxygen sensing response of hot-spots developed on short Er123 ceramic rods of around 12 mm length synthesized using standard solid-state reaction. All the sensor rods showed increase in output current with increasing voltage followed by sudden reduction in output current and appearance of hot spot. After appearance of hot spot, for each rod, output current was observed to decrease gradually with increasing voltage with the slope of the I-V curve gradually approaching zero. Output current after the hot spot formation showed sensitivity to oxygen partial pressure, pO2 between 1 to 100 kPa. Addition of 30 wt. % BaAl2O4 reduced the fluctuation of current and increased the sensitivity for pO2 below 10 kPa. In addition, overshoot current was also reduced and resulted in improvement of response time from around 10 s to 5 s. Our result also showed that minimum power consumption was significantly reduced in the Er123 rods with 30 wt. % BaAl2O4.